The Community Preparedness Education and Training Program in Facing Earthquake Disasters: literatur review - Pusparini Anggita Ayuningtyas; Sri Setiyarini; Syahirul Alim (Universitas Muhammadiyah Surakarta, 2023)
Disasters due to earthquake natural events can have an impact on the community so that people who live in disaster-prone areas are the most disadvantaged parties. The community as a disadvantaged party must be equipped with disaster preparedness, one of which is a disaster risk reduction program. The purpose of this scooping review is to determine the description of the implementation of the earthquake disaster preparedness education and training program in the community. This research is a scooping review using Prisma flow chart in its implementation. The results of this study showed significant results in all articles (n=10) in improving community preparedness in earthquake disaster risk reduction. The methods used were the latest methods (virtual reality, animated videos, and games) and manual methods (lectures, discussions, and reading) with material on disaster concepts, management, and first aid. This research concludes that the role of the community and the importance of disaster preparedness education for the community is very important to be provided by conducting the latest or modern methods for more effective results.